Analisis Usability Website Search Buddy Menggunakan Metode WEBUSE - Pondaag, Wendy; Rahman, Syaiful; Arianti (STMIK KHARISMA Makassar, 2024)
Search Buddy is a website-based application developed to help people find services online which can be found at url address www.searchbuddy.my.id. Research was conducted to analyze the usability level of the Search Buddy website. The approach that will be used to test the usability is the WEBUSE method because the WEBUSE method is specifically designed for web-based systems. The WEBUSE method produces an average value of 0.648 which indicates that the Search Buddy website is at the Good usability level. Therefore, it can be concluded that the website is well received and meets the needs of its users while using it.